2011
DOI: 10.1111/j.1365-2435.2011.01897.x
|View full text |Cite
|
Sign up to set email alerts
|

Egg hormones in a highly fecund vertebrate: do they influence offspring social structure in competitive conditions?

Abstract: Summary1. Social status can vary considerably among individuals and has significant implications for performance. In addition to a genetic component, social status may be influenced by environmental factors including maternal effects such as prenatal hormone exposure. Maternal effects on traits determining social status have previously been examined in species where mothers provide parental care for relatively few offspring and therefore directly influence postnatal development. However, the generality of conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 55 publications
1
40
0
Order By: Relevance
“…Maternal cortisol plays an important organizational role during early development in fish, and cortisol treatment of eggs or embryos alters both physiology and behaviour of the developing young (e.g. Sloman, 2010;Burton et al, 2011;Li et al, 2012;Nesan and Vijayan, 2012;Colson et al, 2015;. However, programming of offspring is probably more complex than the action of cortisol alone, because previous studies have found effects of maternal stress even in the absence of increased embryo cortisol levels -for example, on egg size in Neolamprologus pulcher (Mileva et al, 2011) and on swim performance in Oncorhynchus nerka (Sopinka et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal cortisol plays an important organizational role during early development in fish, and cortisol treatment of eggs or embryos alters both physiology and behaviour of the developing young (e.g. Sloman, 2010;Burton et al, 2011;Li et al, 2012;Nesan and Vijayan, 2012;Colson et al, 2015;. However, programming of offspring is probably more complex than the action of cortisol alone, because previous studies have found effects of maternal stress even in the absence of increased embryo cortisol levels -for example, on egg size in Neolamprologus pulcher (Mileva et al, 2011) and on swim performance in Oncorhynchus nerka (Sopinka et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Still, artificial selection programs seem to be able to create genetic strains with altered aggression levels compared to wild salmonid populations, indicating that there actually is a genetic component for the behavioral expression (Huntingford and Adams 2005). Substantial among-sibling variation in behavior has previously been found in brown trout, attributed to the location of the eggs in the egg sac and possibly pre-natal hormone exposure (Burton et al 2011, 2013). Thus, behavioral strategies of individual fry may be depending on embryonal environment, which can vary within females (Jonsson and Jonsson 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Standard metabolic rate (SMR, usually measured in terms of oxygen consumption) is the minimal maintenance metabolic rate of an ectotherm in a postabsorptive and inactive state (so is the equivalent of the basal metabolic rate of an endotherm), and is an integrated measure of the energy expenditure involved in tissue maintenance and organism homeostasis. After controlling for temperature, body size and other sources of variation, SMR often differs by a factor of 2 or 3 between individuals of the same age, sex and species held in similar conditions (Burton et al, 2011). Aerobic scope (AS) is the difference between an animal's SMR and its maximum possible aerobic metabolic rate (MMR) under the same environmental conditions, so that AS represents the capacity of the animal to increase its rate of aerobic metabolism (Fry, 1957(Fry, , 1971).…”
Section: Introductionmentioning
confidence: 99%